THE INTERNATIONALIZATION OF BUSINESS AS AN OPTION IN THE MARKETING STRATEGY OF THE ENTREPRENEUR - Cristina ALPOPI; Eugen BURDUŞ (Management & Marketing)
Both the process of creating a business, but especially during the course thereof, the entrepreneur should consider a future in terms of domestic and international presence. This would require a marketing strategy for attracting and maintaining loyal customers domestic and international, for whose implementation it should be mentioned for specific tactics, identify ways to internationalize the business and choose the most appropriate forms of advertising.